Análise longitudinal da mobilidade ocupacional dos estrangeiros no mercado de trabalho formal brasileiro - Claudia Lima Ayer de Noronha (2018)
This dissertation aims at conducting a longitudinal panel analysis of the occupational mobility of foreigners inserted in the Brazilian formal labor market between 1995 and 2015. The purpose is to understand the factors that influence positively or negatively the occupational trajectory of the foreigners formally employed in Brazil. Some authors, following the Theory of Assimilation, argue that the occupational mobility of immigrants in the labor market varies according to accumulated human capital levels, with demographic variables and, in particular, becomes upward with the length of residence in the country of destiny. Theorists of the Theory of Segmented Assimilation presuppose the idea that modern societies are diverse and segmented and, therefore, the classical theory of assimilation would not cover the numerous trajectories of foreigners in the target market. As a methodology, we used data from the Annual Social Information Ratio (RAIS) of the Ministry of Labor and Employment from 1995 to 2015, from which longitudinal regression models are estimated for the understanding of 14 groups of foreigners. The results showed that there is an average growth of the occupational status of the foreigner with an increase of the time of the foreigner in Brazil, but this growth precedes an initial movement of falling of the status in the first three years of residence in the country. Thus, we find a "J" mobility format for the Brazilian formal market reality. We perceive that this trajectory varies according to the nationality of the worker, and in general, the greater the economic development of the countries of origin, the better the performance of immigrants in the labor market, which translates into greater probabilities of upward mobility. In addition, other variables that have an impact on the mobility of foreigners in the Brazilian formal market are: 1) region of the country where the foreigner is employed; 2) sex; 3) Number of times the foreigner appears in the RAIS bank (proxy of experience in the formal market); 4) length of residence in Brazil; 5) level of education; 6) race.